National network communities in the life support of resource‐type regions - A.V. Orlova; V.E. Kytmanova (Векторы благополучия: экономика и социум)
Relevance. Interethnic relations in multinational States are one of the most pressing problems of our time. Russia is a multinational country, 190 peoples live in it, 46 of which are indigenous and small. Taking into account the diversity of the peoples living in Siberia, it is necessary to respond in time to emerging tensions or interethnic conflicts leading to mass mobilization of the population and confrontations between «us» and «strangers». Aim. To identify the role of national network communities in the life support system of resource‐type regions. Method. Network analysis, which was conducted both "manually" and using the Popsters analytical site to compare the most popular communities. Results. The authors have identified the most popular national communities. An analysis of the information disseminated in them shows that community members mainly talk about customs, events held, and share recipes for national dishes. It can be noted that the topics of posts and reposts most often relate to the daily lives of residents of the regions, that is, virtual communication complements and expands the real one. Conclusions. In the modern world, digital technologies are increasingly influencing the communications of regional residents. This can affect human identification, including national identification. Social networks facilitate the rapid dissemination of information, which creates opportunities of social and political mobilization of resources for both positive activities and destructive behavior. The national color of online communities can make this mobilization particularly acute that is why timely response to information disseminated in them is so important.